Max Weber-Handbuch: Leben - Werk - Wirkung - Müller, Hans-Peter; Sigmund, Steffen (J.B. Metzler Verlag, 2020)
I Zur Biographie -- II Begriffe -- III Werke und Werkgruppen -- IV Diskussion -- Anhang.
Auswahlbibliographie: Seite 487-492
Keywords: Weber, Max